2021
DOI: 10.3390/app11094212
|View full text |Cite
|
Sign up to set email alerts
|

The Processing of Calcium Rich Agricultural and Industrial Waste for Recovery of Calcium Carbonate and Calcium Oxide and Their Application for Environmental Cleanup: A Review

Abstract: Every year a million tonnes of calcium rich agro and industrial waste are generated around the whole globe. These calcium rich waste like finger citron, shells of cockle, mussel, oysters etc., and egg shell are biological sources which have various organic compounds. The inorganic calcium rich waste includes gypsum, dolomite, sludge etc., which are produced in surplus amount globally. Most of these by-products are mainly dumped, while few are used for land-filling purposes which leads to the pollution. These a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 91 publications
2
32
0
Order By: Relevance
“…Gypsum waste can be processed for the recovery of CaS, which ultimately changes to calcium carbonate. A schematic diagram of the process of recovering calcium carbonate from gypsum waste is shown below in Figure 7, as reported by Yadav et al, 2021 [129]. Beer et al [132] attempted to synthesize calcium carbonate nanoparticles from gypsum waste, producing elemental sulfur as a byproduct.…”
Section: Iron Slags/scrapsmentioning
confidence: 95%
“…Gypsum waste can be processed for the recovery of CaS, which ultimately changes to calcium carbonate. A schematic diagram of the process of recovering calcium carbonate from gypsum waste is shown below in Figure 7, as reported by Yadav et al, 2021 [129]. Beer et al [132] attempted to synthesize calcium carbonate nanoparticles from gypsum waste, producing elemental sulfur as a byproduct.…”
Section: Iron Slags/scrapsmentioning
confidence: 95%
“…The speciality of nanomaterials lies in their tunable nanoscale dimensionality, on the basis of which these are considered as one, two or three dimensional [158]. Thus, two-dimensional nanomaterials are typically those materials that have two of their three dimensions restricted to <100 nm [159].…”
Section: Applications Of 2d Nanomaterialsmentioning
confidence: 99%
“…Eggshell is an inorganic material containing three different layers-mammillary, calcareous, and cuticle. Eggshells largely encompass CaCO3 (almost 94% of its total weight), organic matter (about 4%), calcium phosphate (around 1%), and magnesium carbonate (about 1%) [70]. Using XRF analysis, Mabah et al [71] studied the chemical composition of eggshell powder and found that CaO (93.2%) holds the highest percentage among the constituents.…”
Section: Properties Of Eggshell Powdermentioning
confidence: 99%